2005
DOI: 10.1016/s1449-4035(05)70068-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender Analysis and Social Change: Testing the Water

Abstract: This paper uses preliminary findings from an ARC-funded Linkage grant to speculate on the requirements for producing gender analysis as a change process. Gender analysis, commonly associated with gender mainstreaming, is a methodology aimed at ensuring that all projects, programs and policies are gender-inclusive and gender-sensitive. In the Linkage study existing models of gender analysis taken from Canada and The Netherlands are being tested for their usefulness in selected agencies in South Australia and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…Today at the WU, equality is on the agenda but it is peripheral, and its enactment is dependent on discretionary individual efforts. As Bacchi et al (2006) observed, equality as an academic agenda, as advocated by the FC, has been narrowly incorporated into projects such as teaching and research among a small number of individuals within small teaching groups in two (Management and Economics) of the 11 University departments, as well as two scholarships awarded to female faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Today at the WU, equality is on the agenda but it is peripheral, and its enactment is dependent on discretionary individual efforts. As Bacchi et al (2006) observed, equality as an academic agenda, as advocated by the FC, has been narrowly incorporated into projects such as teaching and research among a small number of individuals within small teaching groups in two (Management and Economics) of the 11 University departments, as well as two scholarships awarded to female faculty.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore have no sense of how systematic distortions filter into the analysis, reinforcing rather than resisting axes of oppression. Thus, gender‐based analysis becomes a mode of “othering” (see also Bacchi et al 2005; Carney 2005).…”
Section: Gender Mainstreaming In Canada: What's the Problem?mentioning
confidence: 99%
“…Another key issue with gender-based analysis is its tendency to privilege gender as the primary axis of oppression, neglecting the complexities of social location, understood as the intersections of gender, race, class, ethnicity, sexuality, nation, ability and so on (Bacchi et al 2005;Bacchi and Eveline 2003;Hankivsky 2005Hankivsky , 2007Teghtsoonian 2000; for discussions of ''intersectionality'' and policy studies, see Manuel 2006 andVerloo 2006). Indeed, despite its potential (and explicit commitment) to consider multiple axes of difference (Rankin and Vickers 2001), gender-based analysis has yet to grapple with the complexities of identity, including the ways in which gender mainstreaming itself produces and reproduces gender, thereby reducing its potential to transform social relations.…”
Section: Gender Mainstreaming In Canadamentioning
confidence: 99%
See 2 more Smart Citations